TRADISI MUNJUNG DI DALAM PESTA PERNIKAHAN ADAT JAWA DI DESA AIR PANAS KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Dyah Lupitasari; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Munjung tradition in the wedding party of Java is a serving food tradition in a wedding party. Nowadays, munjung which is used differently with in the past. It was done simple and aimed to the family member only. However it is aimed to the society right now. This tradition is also influenced by the society economic level. The research carried out at Air Panas village, Pendalian IV Koto subdistricts, Rokan Hulu regency and aimed to know how the implementation of munjung tradition between in the past and right now, when the tradition has changed and how the society perspective trought the used of munjung tradition. The research method used in this research is qualitative method. Qualitative method is used to know the fact or reality, condition and focused on the social fenomena. The relation between this research and the method is in this research, it would be know about munjung tradition based on the norm. Therefor researcher will collect the data and facts about it in Air Panas vilage, Pendalian IV Koto subdistricts, Rokan Hulu Regency. The data collection technique used are interview and observation. The data analysis technique are collecting the data, analized the data, the result finding, condusions and recommendation . Based on the result finding, the used of munjung tradition has changed from the first aim and the used and motivation of the implementation. Giving help is purposed to take a feedback in the future in munjung tradition, the sincerity in giving help is already vanish which is it was the first aim of this tradition. The changing of the used of this tradition was caused the new tradition or culture from the other influenced this tradition and the level of society economic. Therefor, there is a consumtive society culture. The other findings is about the implementation of munjung tradition. This tradition is not only used for wedding party, but also for other party such as khitanan, syukuran, akekah and some of wirid in once a week.Key words: Social changing, giving and feedback, Munjung tradition in wedding party of Java.